Short Communication: Strong genetic differentiation of the endemic rosin-producing tree Styrax sumatrana (Styracaceae) in North Sumatra, Indonesia - HENTI HENDALASTUTI RACHMAT; ARIDA SUSILOWATI; DENI ELFIATI; KANSIH SRI HARTINI; WIZA NONI FARADILLAH (Biodiversitas Journal of Biological Diversity, 2017)
Rachmat HH, Susilowati A, Elfiati D, Hartini KS, Faradillah WN. 2017. Short Communication: Strong genetic differentiation of the endemic rosin-producing tree Styrax sumatrana (Styracaceae) in North Sumatra, Indonesia. Biodiversitas 18: 1331-1335. Styrax sumatrana is an economically important rosin-producing tree endemic to North Sumatra, Indonesia. Distribution of this species is very limited, and the high rate of forest degradation in Sumatra is increasing the necessity for conservation. To quantify genetic variation and population structuring, we collected individuals from 3 populations namely Pakpak Bharat, Humbang Hasundutan (Humbahas) and Tapanuli Utara in which each of the population was represented by 10 individuals. However, the successful rate of amplification was varied among populations and for later analysis, we only took an account those sequences showing clear electropherograms and disposed those which showed ambiguity. We sequenced trnL-trnF chloroplast DNA (cpDNA) region yielded 941 bp after alignment. The trnL-trnF assigned the species into 4 haplotypes in which Pakpak Bharat was differentiated significantly and not shared any similar haplotypes with two others populations. Humbahas and Tapanuli Utara was shared one common haplotype. Mean nucleotide diversity at silent sites ranged 0 - 3.33 x 10-3, while nucleotide diversity at non-synonymous site ranged 0 - 5.9 x 10-4. Strong genetic differentiation was also found among 3 origin populations, with the highest pairwise genetic differentiation found on Pakpak Bharat and Tapanuli Utara (FST= 0.80952). Clear and apparent genetic structuring was possibly caused by geographical barriers such as highland and mountain ranges (Bukit Barisan mountain ranges) which acted as effective barriers to gene flow among population. The findings suggest that conservation efforts should focus on every population because each of the population maintains distinct genetic identity.